Communication Management in Education (SIMPE) - Kasmadi, Jon; Anwar, Kasful; Shalahudin, Shalahudin (Pusdikra Publishing, 2024)
This article aims to explain the context of education and the importance of communication, explain relevant communication theories in education, and explain the role of technology in improving educational communication. The research methodology used in this research is library research. Primary sources are sources that provide data directly from the first hand or are original sources. Secondary data is in the form of books related to the subject matter. The steps of library research are identifying several key terms, finding literature, critically evaluating and selecting literature, organizing literature, and reporting literature summaries. The results show that good communication can strengthen cooperation in decision-making, policy implementation, and evaluation of the education process. Communication management plays a role in education. Good communication between teachers and students, as well as between all parties involved in the educational process will help create a harmonious learning environment.